Erdheim Chester Disease treated successfully with cladribine. (2016) - Azadeh, Natalya; Tazelaar, Henry D.; Gotway, Michael B.; Mookadam, Farouk; Fonseca, Rafael
Abstract: A 61-year-old previously healthy male with a history of progressive fatigue, lower extremity edema, and dyspnea for 4 months was hospitalized with pericardial and pleural effusions (Figure 1A, B). Lung, pleural, and pericardial biopsies were consistent with Erdheim-Chester disease. He was treated with systemic steroids, and ultimately tried on PEG-interferon. He deteriorated clinically and the disease progressed to include CNS manifestations. Ultimately he was treated with Cladribine, at a dose 0.014 mg/kg on day 1, followed by 0.09 mg/kg/day = 6.4 mg IV for 6 additional days. He received 2 further cycles of 0.14 mg kg/day for 7 days (1 month apart). After 3 cycles he improved significantly both clinically and radiographically. Six months post-treatment objective testing showed improvement in cardiac, neurologic, and pulmonary disease. Erdheim Chester Disease (ECD) is a rare non Langerhans cell histiocytosis. Only several hundred cases have been reported in the literature. Treatment for ECD is reserved for those with symptomatic disease, asymptomatic CNS involvement, or evidence of organ dysfunction. There is no standard treatment regimen: Current options include corticosteroids, Interferon alpha (IFN), systemic chemotherapy, and radiation therapy. The occurrence of the V600EBRAF mutation in about 50% of patients can make these patients amenable to targeted therapy with BRAF kinase inhibitors (e.g. Vemurafenib). More recently the presence of N/KRAS, and PIK3CA mutations have provided further rational for targeted therapies. The cytokine profile in patients with ECD suggests monocyte activation cladribine, a purine analogue toxic to monocytes, has also been studied as a treatment for ECD, especially in patients who test negative for the BRAF mutation.